2008
DOI: 10.1177/0011000008315975
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, Depression, Loneliness, and Life Satisfaction

Abstract: This study investigates the cross-cultural construct validity of perfectionism using the Chinese translation of the Almost Perfect Scale—Revised (APS-R; Slaney, Mobley, Trippi, Ashby, & Johnson, 1996) with 509 Chinese high school students from Hong Kong. The factor structure of the Chinese APS-R and correlations between the APS-R subscales and measures of Depression, Satisfaction with Life, and Loneliness are examined. Participants are grouped into three clusters—adaptive and maladaptive perfectionists and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
2
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 55 publications
8
81
2
10
Order By: Relevance
“…Mobley, Slaney, and Rice (2005) performed analyses of the APS-R item responses from 342 academically talented middle school students and they found that three factors emerged via exploratory factor analyses, but goodness-of-fit criteria fell just below the criteria for acceptability. Similarly, Wang et al (2009) …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mobley, Slaney, and Rice (2005) performed analyses of the APS-R item responses from 342 academically talented middle school students and they found that three factors emerged via exploratory factor analyses, but goodness-of-fit criteria fell just below the criteria for acceptability. Similarly, Wang et al (2009) …”
Section: Discussionmentioning
confidence: 98%
“…It is not very surprising when findings are reported indicating that perfectionists with high levels of discrepancy on the APS-R also have elevations on measures that explicitly tap some component of dissatisfaction such as measures of life satisfaction (see Gilman & Ashby, 2003;Gnilka, Ashby, & Noble, 2013;Grzegorek, Slaney, Franze, & Rice, 2004;Pearson & Gleaves, 2006;Wang, Yuen, & Slaney, 2009). …”
Section: How Should Discrepancy Be Assessed In Perfectionism Researchmentioning
confidence: 99%
“…The validity of the APS-R has been explored in several culturally diverse populations, and translated to various languages including Chinese, Asian, Indian, African American, and Turkish samples (e.g., Aydin;2013;Yang et al, 2007;Mobley, Slaney, & Rice, 2005;Slaney, Chadha, Mobley, & Kennedy, 2000;Slaney, Mobley, Trippi, Ashby, & Johnson, 1996;Ulu, 2007;Ulu, Tezer, & Slaney, 2012;Wang, Puri, Slaney, Methikalam, & Chadha, 2012;Wang, Slaney, & Rice, 2007;Wang, Yuen, & Slaney, 2009). Further, a short version of the scale that includes 8 of its items and represents standards and the discrepancy was tested and found to have similar characteristics (Rice, Richardson, & Tueller, 2014).…”
Section: Kira Et Al Psychologymentioning
confidence: 99%
“…It can be said that the perfectionism expectation of the instructors from the people around them motivate these people in the positive way and that other-oriented perfectionism perception is desired and healthy. However, the fact that the expectation of perfectionism is healthy and that their interaction with others is good have led to a decrease in the social emotional loneliness levels of the instructors (Chang, Sanna, Chang & Bodem, 2008;Wang, Yuen & Slaney, 2009). Naturally, this can cause them to feel lonely if the instructors feel responsible, expect others to be perfect as well and strive to achieve this.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…Öğretim elemanlarının etrafındaki insanlardan mükemmeliyetçilik beklentisinin bu insanları olumlu yönde motive ettiği ve başkalarından beklediği mükemmeliyetçilik algısının istenen, sağlıklı yönde olduğu söylenebilir. Nitekim bu mükemmeliyetçilik beklentisinin sağlıklı olması etrafındakiler ile etkileşiminin iyi olması öğretim elemanlarının sosyal duygusal yalnızlık düzeyinde azalmaya yol açmıştır (Chang, Sanna, Chang & Bodem, 2008;Wang, Yuen & Slaney, 2009). Öğretim elemanları kendisini sorumlu hissedip kendi gibi başkalarının da mükemmel olmasını bekliyor ve bunun için çaba sarf ediyorsa doğal olarak bu durum onların kendilerini yalnız hissetmemelerine neden olabilir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified